2023
DOI: 10.1002/ep.14217
|View full text |Cite
|
Sign up to set email alerts
|

Rice yield and carbon dioxide emissions in a paddy soil: A comparison of biochar and polystyrene microplastics

Abstract: Biochar has been suggested as a soil supplement to improve soil fertility. The world is covered in microplastics (MPs). A pot greenhouse experiment was carried out to examine the effects of polystyrene (PS), sugarcane bagasse biochar (SBB), and their interactions (PS × SBB) on the CO2 emission and rice yield in a rice paddy calcareous soil. The largest CO2 emissions occurred 35–40 days following rice planting, which corresponds to the tillering stages of rice growth. Higher CO2 emissions were detected after SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Soil modification through the application of biochar and organic fertilizer emerges as a viable alternative to enhance paddy yield in rainfed conditions (Rassaei, 2022(Rassaei, , 2024. Rainfed areas typically include critical zones vulnerable to water insufficiency, posing challenges to the growth and yield of plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil modification through the application of biochar and organic fertilizer emerges as a viable alternative to enhance paddy yield in rainfed conditions (Rassaei, 2022(Rassaei, , 2024. Rainfed areas typically include critical zones vulnerable to water insufficiency, posing challenges to the growth and yield of plants.…”
Section: Discussionmentioning
confidence: 99%
“…To address the numerous challenges faced by rainfed areas, the application of soil amendments, specifically through biochar and organic fertilizer, emerges as a viable strategy to optimize rice growth while maintaining soil water availability (Głąb et al, 2020;Ansari et al, 2023). Biochar, primarily derived from the pyrolysis process involving the combustion of biomass or organic material under limited oxygen conditions and low temperatures (≤700°C), plays a crucial role in enhancing soil water retention and reduce nitrous oxide emission (Mukhtar et al, 2023;Rassaei, 2023Rassaei, , 2024. Physically, biochar is highly porous, thus its application to soil is considered to improve a range of soil physical and chemical properties including soil moisture content, plant available water content (PAWC) (Hardie et al, 2014), water retention capacity and nutritional status of rhizosphere (nitrogen, phosphorous, and potassium) (Ghassemi-Golezani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has highlighted various benefits of biochar use. For example, sugarcane bagasse biochar (SBB) has been utilized to counteract the negative effects of polystyrene micro plastics in rice ecosystems, resulting in reduced methane emissions and improved yield and biomass production [15]. Similarly, SBB has been applied to enhance the growth of corn and rice in soils contaminated with lead and cadmium, leading to increased shoot and root dry weights and demonstrating its effectiveness in remediating polluted soils [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…23 MPs can alter soil structure and characteristics, as well as plant performance, disrupting the indigenous microbial population. 18 Moreover, a recent study conducted by Rassaei 24 found that the application of PS negatively impacted the growth of rice plants, resulting in slower growth, decreased height, grain yield, and biomass.…”
Section: Introductionmentioning
confidence: 99%